'Technologies of the self and other': how self-tracking technologies also shape the other. Issue 2 (30th April 2019) - Gabriels, Katleen; Coeckelbergh, Mark
Abstract : Purpose: This paper aims to fill this gap (infra, originality) by providing a conceptual framework for discussing "technologies of the self and other, " by showing that, in most cases, self-tracking also involves other-tracking. Design/methodology/approach: In so doing, we draw upon Foucault's "technologies of the self" and present-day literature on self-tracking technologies. We elaborate on two cases and practical domains to illustrate and discuss this mutual process: first, the quantified workplace; and second, quantification by wearables in a non-clinical and self-initiated context. Findings: The main conclusion is that these shapings are never (morally) neutral and have ethical implications, such as regarding "quantified otherness, " a notion we propose to point at the risk that the other could become an object of examination and competition. Originality/value: Although there is ample literature on the quantified self, considerably less attention is given to how the relation with the other is being shaped by self-tracking technologies that allow data sharing (e.g. wearables or apps such as Strava or RunKeeper).